PRINSIP KOMUNIKASI YANG BAIK MENURUT DOKUMEN ETIKA DALAM KOMUNIKASI - Klau, Adelina Bete; Loce, Feronika Jenifer; Mayabubun, Thadeo Devis; Pangalila, Jufaldo (Department of Theology - Sekolah Tinggi Filsafat Seminari Pineleng, 2024)
The article explored the meaning of effective communication according to the ethical principles outlined in the document